On Geodesics of Tangent Bundle with Fiberwise Deformed Sasaki Metric over Kählerian Manifold - Yampolsky, A. (Журнал математической физики, анализа, геометрии, 2012)
We propose a fiber-wise deformation of the Sasaki metric on slashed and unit tangent bundles over the Kalerian manifold based on the Berger deformation of metric on a unit sphere. The geodesics of this metric have different projections on a base manifold for the slashed and unit tangent bundles in contrast to usual Sasaki metric. Nevertheless, the projections of geodesics of the unit tangent bundle over the locally symmetric K ahlerian manifold still preserve the property to have all geodesic curvatures constant. Предложена послойная деформация метрики Сасаки касательного без базы расслоения и единичного касательного расслоения Кэлерова многообразия, основанная на деформации Берже метрики на единичной сфере. В отличие от классической метрики Сасаки, геодезические этой деформированной метрики имеют разные проекции на базу касательного и единичного касательного расслоений. Однако проекции геодезических единичного расслоения над кэлеровим локально симметрическим многообразием все еще сохраняют свойство проектироваться в кривые с постоянными кривизнами.